A critical approach to surrogacy : reproductive desires and demands - Riggs, Damien W.; Due, Clemence (Abingdon, Oxon ; New York, NY : Routledge, 2018)
This comprehensive text makes an important contribution to the study of surrogacy, developing a novel theoretical framework through which to understand the broader social contexts as well as individual decisions at play within surrogacy arrangements. Drawing on empirical research conducted by the authors and supplemented by secondary analyses of media, legislative and public accounts of surrogacy, the book engages with the key stakeholders involved in the practice of surrogacy. Specifically, it canvases the standpoints of women who act as surrogates, intending parents who commission surrogacy arrangements, children born through surrogacy, clinics that facilitate the arrangements, and politicians and journalists who engage with the topic. Through a focus on capitalism as a means of orientating ourselves to the topic of surrogacy, the book highlights the vulnerabilities that potentially arise in the context of surrogacy, as well as the claims to agency invoked by some parties in order to mitigate vulnerability. In so doing, the book demonstrates that the psychology of surrogacy must be broadly understood as an orientation to particular ways of thinking about children, reproduction and economies of labour.
Acknowledgments -- Becoming (dis)oriented -- Conceptual tools -- Women who act as surrogates -- Intending parents -- Children and surrogacy -- Surrogacy clinics -- Media and public discourse -- Ways forward -- References -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Surrogate motherhood; Human reproduction; Parenthood; Capitalism; PSYCHOLOGY / Applied Psychology